2020
DOI: 10.1037/pspi0000194
|View full text |Cite
|
Sign up to set email alerts
|

Episodic simulation reduces intergroup bias in prosocial intentions and behavior.

Abstract: People frequently feel less empathy for and offer less aid to out-groups in need relative to their in-groups.Most attempts aimed at reducing intergroup bias in helping emphasize group-focused cognitions and emotions. However, little is known about how the sensory properties of intergroup episodes informs intergroup decisions. Here we investigate whether episodic simulation (i.e., the ability to imagine events in a specific time and place) (a) increases participants' general willingness to help, and (b) decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
73
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 111 publications
10
73
0
2
Order By: Relevance
“…In another line of research, we found that asking people to vividly simulate a helping scenario increased how much people helped opposing political party members (Gaesser, Shimura, & Cikara, 2019). Particularly surprising was that scene vividness (rather than the vividness of the person participants imagined helping) and perspective-taking independently drove increases in helping.…”
Section: Reducing Perceptions Of Coalitional Cohesion Via Individuationmentioning
confidence: 82%
“…In another line of research, we found that asking people to vividly simulate a helping scenario increased how much people helped opposing political party members (Gaesser, Shimura, & Cikara, 2019). Particularly surprising was that scene vividness (rather than the vividness of the person participants imagined helping) and perspective-taking independently drove increases in helping.…”
Section: Reducing Perceptions Of Coalitional Cohesion Via Individuationmentioning
confidence: 82%
“…This body of evidence is consistent with research on the roles of simulations in cognitive processes more generally, which has shown that we use modality-specific knowledge from previous experiences to understand and navigate the complex world around us. Indeed, simulations of possible actions and interactions have been shown to play a role throughout central areas of psychology, for example, in prejudice reduction, prosocial behavior, action control, and episodic future thinking (e.g., Atance & O’Neill, 2001; Crisp & Turner, 2009; Gaesser, Shimura, & Cikara, 2020), and they are likely to also play a role in consumer behavior more generally. Thus, it is not surprising that simulations also affect motivated behavior in the domain of health.…”
Section: Discussionmentioning
confidence: 99%
“…When scene imagery and perspective taking were entered into the same model for predicting willingness to help, we observed evidence of a multipath scene-by-mind model for the prosocial effect of episodic processes (Figure 3). Indeed, recent evidence in collaboration with Mina Cikara's lab revealed that this model extends to both in-group and out-group targets in need ( Figure 3C), suggesting that the connection between scenes and minds may be robust enough to overcome intergroup bias (Gaesser, Shimura, & Cikara, 2019)--and perhaps help to mitigate some of the antisocial effects of perspective taking backfiring when an individual is threated by the mental perspective of an outgroup member (Sassenrath, Hodges, & Pfattheicher, 2016). subsystem (specifically the anatomically defined hippocampus and parahippocampus) and the RTPJ (independently defined using a theory of mind functional localizer) predicted willingness to help judgments, such that activity in the parahippocampus, hippocampus, and RTPJ regions was more strongly associated with willingness to help in the episodic conditions (i.e., imagine or remember a helping event) compared to non-episodic control conditions (Gaesser, Hirschfeld-Kroen, Wasserman, Horn, & Young, 2019).…”
Section: Episodic Representation Can Heighten Mentalizingmentioning
confidence: 92%
“…Evidence of manipulating episodic simulation and memory influencing mentalizing comes from a series of recent studies on prosocial decision making. My collaborators and I have found that directing people to imagine and remember episodes of helping a person in need can increase prosocial intentions (i.e., willingness to help) in that situation compared to conditions that control for exposure to the person in need and conceptual priming of helping (Gaesser, DiBiase, & Kensinger, 2017;Gaesser, Dodds, & Schacter, 2017;Gaesser, Horn, & Young, 2015;Gaesser, Keeler, & Young, 2018;Gaesser & Schacter, 2014;Gaesser, Shimura, & Cikara, 2019;Sawczak, McAndrews, Gaesser, & Moscovitch, 2019). Imagining and remembering specific helping episodes increases willingness to help compared to visualizing the media website the story of need came from (e.g., blogs, twitter, and a newspaper) and discussion board comments recommending how the person in need could be helped.…”
Section: Episodic Representation Can Heighten Mentalizingmentioning
confidence: 99%